Sex and Population Drive Interindividual Variations in a Cognitive Task Across Three Populations of Wild Zebrafish - Daniel, Danita K.; Bhat, Anuradha (Frontiers in Psychology, 2022)
Animal personality refers to the consistency of variation in behavior among individuals which may be the driving force behind variations in complex behaviors as well. Individual personality could predict how well an organism would perform in behavior and cognition related tasks, as well as survive and thrive in its environment. Therefore, we would expect inter-individual variations in many behaviors, which would persist even if habituation to the experimental setup occurs, which generally results in convergence of behavior (i.e., the difference between individuals becomes less pronounced). Our study used wild-caught zebrafish (Danio rerio) from three natural habitats with differing ecological regimes, to understand how consistency and repeatability in specific traits such as boldness, exploration, and spatial ability varies across and within populations even when habituation causes change in behavior. We found that the extent of individual variation differs between populations, with dynamic habitats showing similar repeatability. This indicates that habitat conditions are important drivers of individual variation in addition to other factors, such as sex or size of individuals within populations. Although we found that sex and size played an important role within some populations for some behaviors, in others, the variation was likely caused by other factors (for example, ecological factors such as vegetation and/or resource availability), for which we have not accounted. This study underlines the importance of studying inter-individual differences as the phenomenon that underpins multiple behavioral traits and explains the possible role of environmental and inherent factors that drive these differences.